With this ring [large type] - Clipston, Amy (Thorndike Press large print Christian romance series., 2025)
"Bestselling author Amy Clipston transports readers back to the picturesque town of Flowering Grove, North Carolina, in this heartwarming contemporary romance"-- Provided by publisher